2020
DOI: 10.1111/1440-1681.13226
|View full text |Cite|
|
Sign up to set email alerts
|

Metformin alleviates renal injury in diabetic rats by inducing Sirt1/FoxO1 autophagic signal axis

Abstract: Diabetic nephropathy (DN) is the major microvascular complication of diabetes mellitus and the most important cause of end‐stage renal disease worldwide. Metformin is the preferred oral hypoglycaemic drug for type 2 diabetes mellitus (T2DM). Recent studies have shown that besides lowering blood glucose, metformin also has protective effects on renal function, but its mechanism is not clear. In this study, we established a diabetic rat model by high‐fat feeding combined with intraperitoneal injection of strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…Autophagy impairment has been implicated in the pathogenesis of DN [ 1 , 57 ]. Importantly, emerging evidence suggests that targeting the autophagy pathway to activate and restore the autophagy activity is renoprotective against DN [ 8 , 58 , 59 ]. In this regard, we demonstrated that P2Y2R deficiency significantly enhanced autophagy activity, which was altered in DN, by increasing autophagy flux (LC3B-II and p62) and expression of other autophagy-related proteins (ATG5, ATG12, Beclin-1).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy impairment has been implicated in the pathogenesis of DN [ 1 , 57 ]. Importantly, emerging evidence suggests that targeting the autophagy pathway to activate and restore the autophagy activity is renoprotective against DN [ 8 , 58 , 59 ]. In this regard, we demonstrated that P2Y2R deficiency significantly enhanced autophagy activity, which was altered in DN, by increasing autophagy flux (LC3B-II and p62) and expression of other autophagy-related proteins (ATG5, ATG12, Beclin-1).…”
Section: Discussionmentioning
confidence: 99%
“…Metformin alleviated inflammation of mesangial cells [ 183 ], which was related to upregulated glucagon-like peptide-1 (GLP-1) receptor expression [ 184 ]. The Sirt1/Foxo1 signal pathway was focused on demonstrating the antioxidative stress effect of metformin subsequently with the activation of autophagy in diabetic rats and high-glucose-induced mesangial cells [ 185 , 186 ]. Increasing PGC-1 α expression in high-glucose-induced TECs and suppression of AKT and mTOR activation in proteinuria induced TECs, subsequently followed by augmented autophagy and mitochondrial dynamics or ER stress that contributed to the renoprotective effects of metformin in DN [ 187 , 188 ].…”
Section: Potential Therapeutic Strategy Targeting Accelerated Kidnmentioning
confidence: 99%
“…Autophagy is a protective mechanism for DKD and is regulated by AMPK and silent mating type information regulation 2 homolog 1 (Sirt1). Sirt1 is a NAD + -dependent deacetylase and increases the expression of FoxO1, a transcription factor that can reduce oxygen-free radicals by inducing autophagy [ 75 , 76 ]. Therefore, the AMPK and Sirt1/FoxO1 axis has been suggested to be a protective signaling pathway in autophagy.…”
Section: Basic Mechanisms Underlying the Effects Of Metformin On Dmentioning
confidence: 99%
“…Therefore, the AMPK and Sirt1/FoxO1 axis has been suggested to be a protective signaling pathway in autophagy. Metformin has been shown to attenuate renal fibrosis and histological changes in the glomerulus via autophagy by activating the AMPK/Sirt1/FoxO1 signaling pathway [ 76 , 77 ].…”
Section: Basic Mechanisms Underlying the Effects Of Metformin On Dmentioning
confidence: 99%